DEVELOPMENT AND FORMATION OF STUDENTS' CREATIVE POTENTIAL IN LEARNING A FOREIGN LANGUAGE THROUGH THE USING OF PROJECTIVE TECHNOLOGIES IN THE CLASSROOM - Ремська, Юлія (SWorldJournal, 2025)
The article examines the issue of developing students' creative potential when learning a foreign language. In the context of globalization and the growing importance of intercultural communication, foreign language skills become extremely important and